1996
DOI: 10.1021/jp960650i
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Chlorophyll a at the Gas−Water Interface in Pure and Mixed Monolayers. An Evaluation of Interfacial pH

Abstract: The stability of chlorophyll a, Chl a, in neat and mixed lipid monolayers at the nitrogen-water interface has been measured using Langmuir trough and HPLC techniques. In neat monolayers, at subphase pH less than 8, Chl a degrades rapidly to produce pheophytin a, Phe a. Above this pH, Chl a appears to hydrolyze, giving a new product, Chl a hyd , spectroscopically similar to the parent compound. This latter process appears to involve alteration at the pentanone ring peripheral to the porphyrin structure. For mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…Thus, some interactions between the lipid and the anions exist, suggesting that this zwitterionic lipid behaves like a partially positively charged compound. This was already pointed out by evaluation of a local pH close to a phosphatidylcholine monolayer . More precisely, the isotherm is shifted toward larger molecular areas when the Keggin polyanion concentration is increased.…”
Section: Resultsmentioning
confidence: 55%
“…Thus, some interactions between the lipid and the anions exist, suggesting that this zwitterionic lipid behaves like a partially positively charged compound. This was already pointed out by evaluation of a local pH close to a phosphatidylcholine monolayer . More precisely, the isotherm is shifted toward larger molecular areas when the Keggin polyanion concentration is increased.…”
Section: Resultsmentioning
confidence: 55%
“…However, the carotenoids of HPCD-treated carrot juices were stable (Zhou et al, 2010). The oxidation of ascorbic acid (Mingotaud et al, 1996) and polyphenols (Corrales et al, 2008) could also lead to the color change as well. No significant difference was detected for the ascorbic acid and polyphenols of HPCD-treated apple juice and melon juice (Gasperi et al, 2009;Chen et al, 2010).…”
Section: Downloaded By [Laurentian University] At 18:54 07 December 2014mentioning
confidence: 99%
“…Moreover, such interactions may also modify the reactivity of chemical groups, as for protonation or acid−base reactions, which call out the concentration of the H 3 O + ions near the interface. Numerous works indicate that there is a significant difference between the pH at the interface with respect to the subphase pH even though it is not supported by direct or clear experimental evidence. Some authors have reported on X-ray photoelectron and infrared spectroscopies 2 and neutron activation analysis 3 measurements of deposited Langmuir−Blodgett multilayers. However, the transfer onto a solid substrate can induce a strong modification of the polar headgroups (partially due to dehydration) as we have recently shown on cadmium arachidate monolayer .…”
Section: Introductionmentioning
confidence: 99%
“…However, the transfer onto a solid substrate can induce a strong modification of the polar headgroups (partially due to dehydration) as we have recently shown on cadmium arachidate monolayer . On the other hand, in situ experiments have been carried out by fluorescence spectroscopy, chemical stability of a molecular probe, surface potential, ,, X-ray reflectivity, and X-ray diffraction . However, the first two methods require external probes, which may be perturbative, while the results obtained with the other methods strongly depend on the model used.…”
Section: Introductionmentioning
confidence: 99%